Effects of Peer Pressure and Competition on Academic Performance of Selected Grade 12 HUMSS Strand Students in Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Peer pressure is a direct influence on people by peers or the effect in an individual who gets encouraged to follow their peers by changing their attitudes, values, or behavior to conform to those of the influencing group or individual. Peer pressure can decrease one’s confidence. It can affect the lives of students drastically. Competition is done by several people or organizations that are trying to do their best better than others. The eagerness to be on top and to be number one is always in your mind. No unity is formed in your section because all want to be on top. This paper will discuss the effects of peer pressure and competition among students. The researchers will also study how peer pressure affects student behavior and performance and its outcome. This study is quantitative research with the use of descriptive research design. We use purposive sampling based on the characteristic of a population and the objectives of the study. Data are gathered using a survey questionnaire. The study has examined the effects of peer pressure and competition on the academic performance of selectedGrade 12 Humanities and Social Sciences Strand students. The specific objectives include determining that people of all ages are vulnerable to peer pressure and competition, and several factors trigger the respondents. The study focuses on respondents aged 15–18 years old. Our respondents consisted of 55.8% female and 44.2% male. Thus, females got a higher percentage of respondents rather than males. The grades between 91 up to 95 got the highest percentage, which is 87.6% because we have purposively selected students with honors. The following conclusions have been drawn. Being frustrated can affect the behavior of any student because of the pressure that they encounter due to their peers. Having good communication can motive the students and lead them in a good relationship with others. Feeling the pressure can lead to distraction; thus, the student may lose interest in learning. Feeling of loneliness or being out of place can cause mental health problems in a student. Overall, peer pressure and competition greatly affect students’ academic performance, but this effect differs from students regarding how are they going to reflect it on their lives. Some students have bad outcomes, whereas some have positive ones. Peer pressure and competition affect the students positively by making students more competitive and making them actively participate in any activity regardless of its positive outcome. Some students experienced being down because of peer pressure and competition, thereby causing them to isolate themselves from others.
Keywords: : academic performance, competition, peer pressure